Dynamic interaction of urban development and rural–urban migration: an application of integrated urban metabolism analysis tool (IUMAT) for sustainable city planning. Issue 2 (24th March 2021) - Roy, Neha Chhabra; Thangaraj, Viswanathan
Abstract : Purpose: This study aims to gauge the effect of rural–urban migration and its challenges on the urban development of Bengaluru. This study examines the driving forces behind urbanization and its impact on social, economic and environment areas. The research helps to establish the sustainable city planning, after evaluation of specific challenges of zones, and this mitigation will optimize government investment and reduce cost. Design/methodology/approach: Bengaluru is used as a study area to examine the interaction of migration and urban development. The study covers the period between 2011 and 2019. Panel data analysis is applied to measure the effect of urban development indicators on urban migration. The authors applied the integrated urban metabolism analysis tool to quantify the urban development indicators and identified the most critical areas for migrants. Later, authors proposed mitigation measures based on alternate scenario approach. Findings: The authors found that there is a mixed effect of urban migration on urban development across various zones in Bengaluru. Besides, the authors suggest how planned collaboration should play a significant role in urban planning and optimize city planning judiciously. Effective mitigation measures should be developed based on zone-specific core issues, and practical trainings, research, public awareness campaigns and skill up-gradation of migrants would enhance the socio-economic and environmental conditions. Research limitations/implications: The study will support the ongoing and upcoming initiatives launched by the Government of India i.e. Awas Yojna, Atmanirbhar Bharat and Swach Bharat. Practical implications: The structured city planning suggested in the study will help to save wastage of resources and cost and time of developers and policymakers. This will also help to upgrade the status of migrants and enhance the ambience of city around social, economic and environment fronts. Originality/value: The first of its kind of innovative model mapped in the study area establishes a link between strategic city planning under rural–urban migration and urban development.